Writing a postgraduate literature review: challenges, concerns and some advanced approaches - Miliauskaitė, Jolanta; Čaplinskas, Albertas (Lietuvos matematikos rinkinys, 2013)
The aim of the paper is twofold. On the one hand, it reflects the experience gained supervising master and doctoral theses/dissertations in various Lithuania universities and highlights some common challenges and concerns. On the other hand, it acknowledges with some advanced library research methods and that facilitate writing of postgraduate literature reviews.
Keywords: library research; systematic literature review; systematic mapping studies; tertiary review